Revealing the SIDA culture in Manggarai on an accrualbased accounting perspective - Leopold Melkiano Triangga Dawu; Susana Purnamasari Baso; Maria Odriana Veronica Moi (The Indonesian Accounting Review, 2022)
From the point of view of accounting science, the culture of giving donations that causes a form of payment and occurs in community groups can refer to the recognition of transactions called the basis of accounting. The culture of paying between families in community groups has affected the structure of society itself. This study aims to examine the "SIDA" tradition that occurs in Manggarai from an accounting point of view. Manggarai is one of the districts in East Nusa Tenggara, which also has a culture of payment obligations called Sida. This study uses qualitative methods through observation and in-depth interviews with community groups in Manggarai. The culture of sida in this study is sidalaki (donations for wedding events), sidamata (gifts for death events), and sidapenti (donations for thanksgiving events). The results show that the culture of sida, Sidalaki (wedding ceremony donations), sidamata (death event donations), and sidapenti (thanksgiving event donations) in Manggarai, implies accrual-based accounting or accrual basis in the process, namely recognition of obligations, income from the sida.